DEVELOPMENT OF A HYPER-CONTENT E-MODULE USING A SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) APPROACH TO TRAIN COGNITIVE AND PSYCHOMOTORY LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTS - Sausan Asy Syifa Madaniah; Prasetyo Listiaji (Jurnal Pembelajaran Sains, 2023)
Education is essential and a right for all Indonesian citizens. The quality of education is seen in student learning outcomes. Based on observations at SMP N 1 Talun, as many as 85.3% of students' cognitive learning outcomes still need to be completed, and learning activities after the COVID-19 pandemic have yet to carry out learning activities that can hone students' psychomotor abilities. The use of teaching materials is also only based on printed package books. Therefore, it is necessary to develop teaching materials to train students' cognitive and psychomotor learning outcomes. Research & Development (R&D) research conducted using the 4D model. This study aims to determine the characteristics and validity of hypercontent e-modules with a STEM approach and the profile of students' cognitive learning outcomes and psychomotor learning outcomes after using e-modules. The average material and media validation results were 95.4% and 97.2%, which received very valid criteria. The cognitive and psychomotor learning outcomes profile shows that 76% and 79% of students get a complete score. Based on these results, hypercontent e-modules with a STEM approach are declared very valid and can train students' cognitive and psychomotor learning outcomes.